Limited Effects of SARS-CoV-2 Pandemic-related Lockdowns and Reduced Population Mobility on Preterm Birth Rates: A Secondary Analysis of Bavarian Obstetric Quality Parameters from 2010 to 2020 - Stumpfe, Florian Matthias; Schneider, Michael Oliver; Hein, Alexander; Faschingbauer, Florian; Kehl, Sven; Hermanek, Peter; Böhm, Julian; Scharl, Anton; Beckmann, Matthias Wilhelm; Staerk, Christian; Mayr, Andreas (Geburtshilfe und Frauenheilkunde, 2022)
Introduction International studies on preterm birth rates during COVID-19 lockdowns report different results. This study examines preterm birth rates during lockdown periods and the impact of the mobility changes of the population in Bavaria, Germany.Material and Methods This is a secondary analysis of centrally collected data on preterm births in Bavaria from 2010 to 2020. Preterm births (< 37 weeks) in singleton and twin pregnancies during two lockdowns were compared with corresponding periods in 2010 – 2019. Fisherʼs exact test was used to compare raw prevalence between groups. Potential effects of two fixed lockdown periods and of variable changes in population mobility on preterm birth rates in 2020 were examined using additive logistic regression models, adjusting for long-term and seasonal trends.Results Unadjusted preterm birth rates in 2020 were significantly lower for singleton pregnancies during the two lockdown periods (Lockdown 1: 5.71% vs. 6.41%; OR 0.88; p < 0.001; Lockdown 2: 5.71% vs. 6.60%; OR = 0.86; p < 0.001). However, these effects could not be confirmed after adjusting for long-term trends (Lockdown 1: adj. OR = 0.99; p = 0.73; Lockdown 2: adj. OR = 0.96; p = 0.24). For twin pregnancies, differences during lockdown were less marked (Lockdown 1: 52.99% vs. 56.26%; OR = 0.88; p = 0.15; Lockdown 2: 58.06% vs. 58.91%; OR = 0.97; p = 0.70). Reduced population mobility had no significant impact on preterm birth rates in singleton pregnancies (p = 0.14) but did have an impact on twin pregnancies (p = 0.02).Conclusions Reduced preterm birth rates during both lockdown periods in 2020 were observed for singleton and twin pregnancies. However, these effects are reduced when adjusting for long-term and seasonal trends. Reduced population mobility was associated with lower preterm birth rates in twin pregnancies.
Keywords: COVID-19; SARS-CoV-2; preterm birth; lockdown measures; preterm delivery